Relationship between flow experience and performance in junior tennis - Koehn, S. (Medicine and Science in Tennis, 2008)
Flow experiences have important implications for performances in both sport and everyday life. Several studies have shown correlations between flow and subjective performance assessments and flow and objective performance outcomes. One limitation of previous investigations was the overall assessment of flow state, measuring flow retrospectively after the end of the training or competition performance. In this pilot study, flow was measured repeatedly in a two-set tennis-training match, in which participants reported their flow state during the match breaks. The purpose of the present study was to examine the relationship between flow and performance outcome. Results revealed similar patterns between flow and performance measurements. The conclusion drawn is that there is a positive association between flow state and performance: stronger flow experiences are linked to better performances. More in-depth studies are needed to corroborate the current findings on the flow-performance relationship.